Sodium Chloride Catalyzed Regioselective Trifluoromethylthiolation of Furans - Ernst, Johannes B.; Rakers, Lena; Glorius, Frank (Synthesis, 2017)
Here, we report the catalytic trifluoromethylthiolation of furans employing sodium chloride as an inexpensive, abundant and ecologically friendly catalyst. The developed method exhibits perfect regioselectivity and a high functional group tolerance. Furthermore, the robustness of the newly developed method was determined by the additive-based Robustness Screen.
Keywords: trifluoromethylthiolation; sodium chloride; bioactive compounds; heterocycles; synthetic methods